Microstructure Evolution of Si Nanocrystals in Si/C Multilayer Films. Issue 1 (January 2018) - Gengrong, Chang; Mingxia, Liu; Fei, Ma; Fuxing, Fu; Binfeng, He; Kewei, Xu
Abstract: Si/C multilayer films deposited by radio frequency magnetron sputtering were post-annealed at 1100 °C for 1 h to produce Si nanocrystals (NCs). X-ray diffraction and Raman spectroscopy were used to analyze the phase composition and atomic vibration spectrum of the multilayer structure. High-resolution transmission electron microscopy was employed to verify the existence of Si NCs and to observe their sizes and morphologies. The results reveal that the Si NCs are formed by solid-phase recrystallization of the nanometer-thick layers of amorphous Si confined between C layers. The NC shape and size could be tuned by changing the modulation ratio of the Si layer and the C layer. When the ratio shifts from 0.5 to 2, the NCs become spherical, elliptical, square, or brick-shaped. This growth mode may be conducive to the design of different Si-based photo-electronic materials.